Genetic and non-genetic factors affecting reproductive performance in exotic rabbit breeds under Egyptian conditions - Farghaly H.M.; El Darawany A.A. (Rabbit production in hot climates, 1994)
Data on 2466 parturitions from 300 Bauscat (BAU), 200 New Zealand White (NZW) and 100 Californian (CAL) purebred does were analysed by fixed and mixed model procedures. The data came from two groups, one imported from Hungary (473) and one locally-born in Egypt (127). The work was carried out to investigate the effects of group, breed, season of birth and parity on reproductive performance. Reproductive performance of the imported does was better than that of the locally-born does. The CAL breed had significantly higher (P less than 0.01) litter size at different periods (birth, 21 and 30 days) and lower litter weight at birth than NZW and BAU breeds. Season of birth showed highly significant (P less than 0.01) effects on preweaning litter size and litter weight. The regression coefficients of litter size at birth, 21 and 30 days on both gestation period and litter weight at birth were highly significant and it was significant for litter weight at birth and at 21 days on gestation period. Heritability of litter size at different ages showed moderate values. The genetic correlations among each litter size and litter weight at different ages were positive and high. The phenotypic correlations among all reproductive performance traits were highly positive. The observed trends of the LZ and LW showed the unfavourable climate conditions depressed performance the locally-born does and indicate that these seem to be undergoing the adaptive process during the period of the study. Improvement of (phenotypic) one of these characters means improvement of other characters at the same time.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)